REVIEW AND ANALYSIS OF ANTHRAX DIAGNOSTIC TOOLS ON THE TERRITORY OF EURASIAN ECONOMIC UNION - Nizkorodova, A.; Maltseva, E.; Berdygulova, Zh.; Naizabayeva , D.; Skiba , Yu. (Eurasian Journal of Applied Biotechnology, 2023)
This review examines anthrax diagnostic tools registered in the national Veterinary Drugs Registers and Medicines and Medical Devices Registers of the Eurasian Economic Union (EAEU). Actually, throughout the entire territory of the EAEU, there are natural soil foci of anthrax, which causes annual cases of infection of animals and people. Continuous monitoring of the epidemiological situation in the EAEU countries should be ensured by modern diagnostic tools. All diagnostic tools used for epidemiological surveillance must be registered in the national registers of the EAEU countries. For all test systems and diagnostic kits included in the registers of the EAEU countries, the authors provide comparative characteristics that reflect the sensitivity and specificity of diagnostic tools. An analysis of various methods for identifying the anthrax pathogen, focused on modern molecular diagnostic technologies, is presented. The authors discuss the most important problems associated with improving the efficiency of modern methods for detecting the bacterium Bacillus anthracis. Some considerations about the shortcomings in certain areas of early diagnosis of the anthrax microbe are also provided. The authors present a number of proposals that should improve the efficiency of the currently available anthrax monitoring system.